Pengembangan Materi Ajar Teks Berita Berbantuan Aplikasi Filmorago Kelas VIII SMP Swasta Dharma Patra Pangkalan Brandan - Diaz Maulana (Universitas Palangka Raya, 2023)
This study aims to, (1) describe the process of developing news text teaching materials based on the Filmorago application, (2) describe the form of developing news text teaching materials based on the Filmorago application, and (3) describe the feasibility of teaching materials for news texts based on the Filmorago application. The development of teaching materials for news texts based on the Filmorago application uses the Borg and Gall model modified by Sugiyono, with stages of potential and problem analysis, data collection, product design, design validation, revision and trial stages. The validation stage includes material expert lecturers and expert lecturers. The sample of this study was 37 grade VIII students of Dharma Patra Pangkalan Brandan Private Junior High School using the Purpossive Sample technique. Data collection techniques with interviews and questionnaires. The research instrument is in the form of a questionnaire sheet validating material experts and media experts using Likert scale calculations. Data analysis uses qualitative descriptive analysis. Research shows that products from Filmorago application-based news text teaching materials get research results with